Preparation method and application of dry repair mud for ceramic repair

In the preparation process of dry sludge for ceramic repair, wet ball milling is used with composite porcelain powder, improvement enhancer and composite fibers, and the moisture content after drying is controlled, the problem of poor adhesion of dry sludge for ceramic repair is solved, and the repaired ceramic has small color difference, strong high temperature resistance, high wear resistance, significantly improved compressive strength and bending strength, extending the service life of the ceramic and improving production efficiency.

CN119841619AActive Publication Date: 2025-04-18GUANGDONG LEXIAN SANITARY WARE CO LTD

Patent Information

Application Number
CN202510050986.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing dry slurry for ceramic repair has poor adhesion, which leads to the uneven color and short life of the repaired ceramics, which seriously affects the production efficiency.

Method used

By wet ball milling of composite porcelain powder, modification reinforcement and composite fibers, and adding a dispersant mixture, a modified thickener and calcium silicate, the moisture content after drying is controlled, and a dry sludge for ceramic repair with improved adhesion and high temperature resistance is prepared.

Benefits of technology

The repaired ceramic has achieved small color difference, strong high temperature resistance, high wear resistance, and significantly improved compressive strength and bending strength, extending the service life of the ceramic and improving production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841619A_ABST
    Figure CN119841619A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ceramics, in particular to a preparation method and application of dry repairing mud for ceramic repairing. According to the invention, the repaired ceramic overcomes the defects of non-uniform color and short service life. The preparation method of the dry repair mud for ceramic repair comprises the following steps: performing wet ball milling on the composite ceramic powder, the improved reinforcing agent and the composite fiber, then adding the dispersant mixture, the modified thickening agent and the calcium silicate for continuous wet ball milling, and drying to obtain the dry repair mud. The dry repairing mud is applied to ceramic body repairing, and the color difference of repaired ceramic is reduced by controlling the dosage of the composite ceramic powder, the proportion of all components in the composite ceramic powder and the ball milling time; due to the addition of the improvement enhancer and the control of the water content, the repaired ceramic does not crack; the wear resistance of the repaired ceramic is improved by controlling the dosage of the composite fiber and dispersant mixture; due to the addition of the modified thickening agent, the water absorption rate of the repaired ceramic is reduced; and the strength of the repaired ceramic is improved by controlling the dosage of calcium silicate and parameters in repairing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a preparation method and application of dry patching mud for ceramic repair. Background Art

[0002] In the ceramic production process, all processes will inevitably cause cracks and brown eyes in the ceramic body. There will also be bumps during transportation between different processes, which will reduce the qualified rate of ceramic products. Therefore, it is very important to repair the ceramic body, which can increase the service life of the ceramic to a certain extent and improve production efficiency. Generally, small defects will be repaired with the raw material mud of the ceramic body itself, which can achieve good results. However, when encountering larger crack defects, the raw material mud of the body can only be used to fill the cracked space of the body. However, the broken particles inside are not connected, and re-calcination is likely to cause cracking.

[0003] Patent CN106083018B discloses a patching mud for ceramic dry blank repair, and its preparation method and application. The invention provides two formulas, and the two formulas are mixed to form patching mud. The patching mud provided by the invention has small drying shrinkage after repair and drying, is consistent with the repaired blank, and the degree of vitrification is close to the water absorption rate of the finished porcelain. However, the patching mud in the invention only changes the proportion of raw materials such as feldspar, quartz, and dolomite, and can only make simple repairs to the blank. The ceramic after firing has low compressive strength and short service life, and is easy to be damaged again at the repaired part.

[0004] Patent CN101717268B discloses a ceramic clay repair blank, its preparation method and repair process. The ceramic clay repair blank prepared by adding auxiliary modified materials in the invention is resistant to stretching, has small shrinkage, and can be perfectly combined with dry clay materials. Due to the unique three-dimensional network structure of the ceramic clay repair blank of the invention, the adhesion between the ceramic clay particles is greatly enhanced, which can not only stabilize the repair part during the drying process, but also can be integrated with the ceramic body during the firing process, and can completely repair the drying cracking of the clay. However, the addition of glass fiber will affect the strength and brittleness of the repair blank, making the repair blank poorly bonded and difficult to repair, and the glass fiber itself is relatively expensive, which increases the production cost.

[0005] In summary, the dry patching mud currently used for ceramic repair still has the disadvantage of poor adhesion, which causes the repaired ceramics to have problems such as uneven color and short life, seriously affecting production efficiency.

[0006] Therefore, a preparation method and application of dry patching mud for ceramic repair are proposed. Summary of the invention

[0007] The purpose of the present invention is to design a preparation method and application of dry patching mud for ceramic repair. The present invention enables the repaired ceramic to overcome the shortcomings of uneven color and short life; the preparation method of the dry patching mud for ceramic repair is: the composite ceramic powder, the improved reinforcing agent and the composite fiber are first wet-milled, and after reaching a certain particle size, a dispersant mixture, a modified thickener and calcium silicate are added to continue wet-milling, and the dry patching mud for ceramic repair is obtained after drying. The present invention applies dry patching mud to the repair of ceramic blanks, and reduces the color difference of the repaired ceramics by changing the amount of composite ceramic powder, the proportion of each component in the composite ceramic powder and the time of ball milling; improves the high temperature resistance of the repaired ceramics by preparing the improved reinforcing agent and controlling the water content of the dry patching mud; improves the wear resistance of the repaired ceramics by changing the amount of the composite fiber and the dispersant mixture and the proportion of each component therein; reduces the water absorption rate of the repaired ceramics by controlling the parameter conditions for preparing the modified thickener; improves the compressive strength and bending strength of the repaired ceramics by changing the amount of calcium silicate and the parameters in the process of repairing the ceramic blank.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] In one aspect, the present invention provides a method for preparing dry patching mud for ceramic repair, wherein the method for preparing dry patching mud for ceramic repair is as follows:

[0010] Putting the discarded porcelain pieces into a pulverizer for pulverization to obtain waste porcelain powder; mixing the waste porcelain powder, green body powder and glaze powder to obtain composite porcelain powder;

[0011] An improved reinforcing agent is obtained by adding an acrylic acid ester copolymer to a mixture of mullite and potassium feldspar for modification;

[0012] Adding diisocyanate to a mixture of methylcellulose and hydroxypropylmethylcellulose for cross-linking reaction to obtain a modified thickener;

[0013] 62-66 parts of the composite ceramic powder, 11-15 parts of the improved reinforcing agent and 3-7 parts of the composite fiber are weighed by weight, and wet-milled for 2h-5h using 30 parts of deionized water as a medium, so that the number of particles with a particle size of 15 μm reaches more than 65%, to obtain slurry A;

[0014] Add 0.6-1 parts of the dispersant mixture, 0.1-0.4 parts of the modified thickener and 0.07-0.1 parts of calcium silicate to the slurry A, and perform secondary wet ball milling for 5h-8h to obtain slurry B;

[0015] The mud B is naturally dried until the moisture content is 13%-17% to obtain the dry mud for ceramic repair.

[0016] Preferably, the waste porcelain powder is recycled from discarded porcelain chips, which can not only reduce environmental pollution, but also save resources, reduce costs, and effectively improve production efficiency.

[0017] Preferably, the weight ratio of the waste porcelain powder, the green body powder and the glaze powder is 5-8:1:0.5.

[0018] Preferably, the chemical composition of the waste porcelain powder is 63.2% SiO2, 18.8% Al2O3, 8.1% CaO, 4.5% MgO, 1.3% Fe2O3, 2.1% K2O, 0.9% Na2O and 1.1% TiO2; the chemical composition of the green body powder is 62.7% SiO2, 27.4% Al2O3, 5.3% CaO, 2.0% MgO, 0.7% Fe2O3, 0.7% K2O, 0.8% Na2O and 0.4% TiO2; the chemical composition of the glaze powder is 61.3% SiO2, 14.5% Al2O3, 13.1% CaO, 2.6% MgO, 1.9% Fe2O3, 3.7% K2O, 2.5% Na2O and 0.4% TiO2.

[0019] Preferably, the preparation method of the improved reinforcing agent is specifically as follows: 14-18 parts of the mullite and 4 parts of the potassium feldspar are ground until the particle size reaches 10 μm to obtain a mixed powder; 1-4 parts of the acrylic ester copolymer and 8 parts of deionized water are added to the mixed powder, followed by stirring for 3-6 hours until the mixture is uniformly mixed to obtain the improved reinforcing agent.

[0020] Preferably, the preparation method of the modified thickener is specifically as follows: adding 2-6 parts of the methyl cellulose and 3 parts of the hydroxypropyl methyl cellulose to 6 parts of deionized water, stirring until uniformly dispersed, to obtain a cellulose mixture; adding 0.5-2 parts of the diisocyanate to the cellulose mixture, stirring for 1 hour, to obtain a thickener precursor; transferring the thickener precursor to a reaction kettle for cross-linking reaction at 115°C-130°C for 3 hours, cooling and centrifugal drying to obtain the modified thickener.

[0021] Preferably, the composite fiber is a mixture of polypropylene fiber, polyester fiber and carbon fiber; the weight ratio of the polypropylene fiber, the polyester fiber and the carbon fiber is 3-7:2:1.

[0022] Preferably, the dispersant mixture is a mixture of polyvinyl alcohol and polycarboxylic acid; the weight ratio of the polyvinyl alcohol to the polycarboxylic acid is 6-9:2.

[0023] Another aspect of the present invention provides an application of dry patching mud for ceramic repair, wherein the steps of applying the dry patching mud to repair a ceramic body are as follows:

[0024] S1: cleaning the cracks of the blank to remove ash and other impurities in the cracks of the blank, wherein the cleaning depth is 1.5-2.5 mm;

[0025] S2: wetting the cracks of the green body with deionized water, and naturally drying the cracks;

[0026] S3: Fill part of the dry patching mud into the crack of the green body and compact it, then continue to fill the dry patching mud until the compacted part is higher than the green body surface around the patching part, and wet the patching part and the surrounding part with deionized water;

[0027] After S4 is naturally dried, the raised part of the surface of the blank is scraped off and the repaired part is polished. Then it is glazed and put into the kiln. It is fired at temperature TE1 for time TI1 to finally complete the ceramic repair.

[0028] Preferably, the height above the surface of the blank around the repaired part in S3 is 1 mm.

[0029] Preferably, the temperature TE1 in S4 is 1100° C.-1140° C.; and the TI1 time is 20-23 h.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. Reduce the color difference of the repaired ceramics by changing the amount of composite porcelain powder, the proportion of each component in the composite porcelain powder and the time of ball milling. The use of waste porcelain powder is the secondary utilization of discarded porcelain pieces, which reduces environmental pollution, saves resources and effectively improves production efficiency; the waste porcelain powder, green body powder and glaze powder are mixed, and the chemical composition is highly similar to the chemical composition of the ceramic green body, which can effectively fill the cracks of the green body and maintain a highly similar color, so that the color difference of the repaired ceramics is small; the ball milling time determines the fineness of the composite porcelain powder. If the fineness is too coarse, the dry patch mud will not be tightly combined with the green body, resulting in a large color difference after calcination. If the fineness is too fine, it is easy to cause secondary cracking after calcination. Finally, the repaired ceramics have no color difference.

[0032] 2. Improve the high temperature resistance of the repaired ceramic by preparing an improved reinforcing agent and controlling the moisture content of the dry patching mud. The mullite in the improved reinforcing agent has the advantages of low shrinkage and low expansion. The repaired ceramic is not easy to crack, which effectively improves the high temperature resistance of the repaired ceramic; adding acrylic copolymer to modify mullite and potassium feldspar effectively improves the adhesion of the dry patching mud, making the combination of the green body and the dry patching mud tighter, not easy to crack after calcination, and increasing the service life; if the moisture content of the dry patching mud is too high, it will increase the difficulty of repair, and it is easy to collapse after calcination, and the repair effect is poor. If the moisture content of the dry patching mud is too low, the green body and the dry patching mud are not easy to bond, and it is easy to cause cracking after calcination, and the high temperature resistance is poor. Finally, the repaired ceramic has strong high temperature resistance and no cracking.

[0033] 3. Improve the wear resistance of the repaired ceramic by changing the amount of composite fiber and dispersant mixture and the proportion of each component. Composite fiber can increase the bonding force between dry patching mud and ceramic body. The mesh structure inside the fiber helps to enhance the adhesion of dry patching mud, which enhances the wear resistance of the repaired ceramic and extends the life of the ceramic. The dispersant mixture disperses each component evenly, preventing the occurrence of agglomeration. There will be no uneven drying during the ceramic body repair process, which enhances the wear resistance and durability of the repaired ceramic. The wear loss of the repaired ceramic in 24 hours is 2.0cm 3 .

[0034] 4. Reduce the water absorption rate of the repaired ceramic by controlling the parameters of the preparation of the modified thickener. The performance of the thickener is improved by cross-linking the mixture of methylcellulose and hydroxypropyl methylcellulose. The viscosity and adhesion of the dry filler are improved by changing the parameters in the preparation process, making the repaired ceramic denser and the surface smoother, thereby reducing the water absorption rate of the repaired ceramic, reducing the erosion of water on the ceramic, and extending the life of the ceramic. The water absorption rate of the repaired ceramic is 0.13%.

[0035] 5. Improve the compressive strength and flexural strength of the repaired ceramic by changing the amount of calcium silicate and the parameters in the process of repairing the ceramic body. Calcium silicate helps to enhance the compressive strength and flexural strength of the repaired ceramic because it can form a more stable phase, thereby improving the overall structural strength of the repaired ceramic. It also has a certain corrosion resistance, which effectively extends the life of the repaired ceramic. By controlling the parameter conditions in the repair, too high firing temperature will affect the internal structure of the ceramic, resulting in reduced compressive strength and flexural strength, and will also cause excessive shrinkage of the ceramic and secondary cracking. Too low firing temperature will cause the dry patch to be loosely combined with the ceramic body, and the compressive strength and flexural resistance at the cracks are low, and the service life is short. The compressive strength of the repaired ceramic is 118.2MPa, and the flexural strength is 28.4MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a compressive strength graph of Example 61, Example 65, Example 68, Example 71, Examples 75-76 and Comparative Examples 10-14 of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Specific reference Figure 1 The present invention provides a preparation method and application of dry patching mud for ceramic repair, and the technical scheme is as follows:

[0039] Example 1

[0040] Putting the discarded porcelain pieces into a pulverizer for pulverization to obtain waste porcelain powder; mixing the waste porcelain powder, green body powder and glaze powder in a weight ratio of 5:1:0.5 to obtain composite porcelain powder;

[0041] 14 parts of mullite and 4 parts of potassium feldspar are ground until the particle size reaches 10 μm to obtain a mixed powder; 1 part of an acrylic acid ester copolymer and 8 parts of deionized water are added to the mixed powder, and then stirred for 3 hours until the mixture is uniformly mixed to obtain an improved reinforcing agent;

[0042] Add 2 parts of methyl cellulose and 3 parts of hydroxypropyl methyl cellulose to 6 parts of deionized water, stir until uniformly dispersed, and obtain a cellulose mixture; add 0.5 parts of diisocyanate to the cellulose mixture, stir for 1 hour, and obtain a thickener precursor; transfer the thickener precursor to a reaction kettle, perform a cross-linking reaction at 115° C. for 3 hours, and obtain a modified thickener after cooling and centrifugal drying;

[0043] The polypropylene fiber, the polyester fiber and the carbon fiber are mixed in a weight ratio of 3:2:1 to obtain a composite fiber;

[0044] The polyvinyl alcohol and the polycarboxylic acid are mixed in a weight ratio of 6:2 to obtain a dispersant mixture;

[0045] 62 parts of the composite ceramic powder, 11 parts of the improved reinforcing agent and 3 parts of the composite fiber were weighed by weight, and wet-milled for 2 hours using 30 parts of deionized water as a medium, so that the number of particles with a particle size of 15 μm reached more than 65%, to obtain slurry A;

[0046] Add 0.6 parts of the dispersant mixture, 0.1 parts of the modified thickener and 0.07 parts of calcium silicate to the slurry A, and perform secondary wet ball milling for 5 hours to obtain slurry B;

[0047] The slurry B is naturally dried until the water content is 13% to obtain the dry slurry for ceramic repair.

[0048] The dry patching mud is applied to the ceramic body repair, and the steps are as follows:

[0049] S1: cleaning the cracks of the blank to remove ash and other impurities in the cracks of the blank, wherein the cleaning depth is 1.5 mm;

[0050] S2: wetting the cracks of the green body with deionized water, and naturally drying the cracks of the green body;

[0051] S3: Fill part of the dry patching mud into the crack of the green body and compact it, then continue to fill the dry patching mud until the compacted part is higher than the green body surface around the patching part, and wet the patching part and the surrounding part with deionized water;

[0052] After S4 is naturally dried, the raised parts of the body surface are scraped off and the repaired parts are polished. Then, glaze is applied and put into the kiln, fired at 1100℃ for 20 hours to complete the ceramic repair.

[0053] Example 2-14

[0054] Referring to the preparation method and application parameter conditions in Example 1, the specific differences are shown in Table 1.

[0055] Table 1 Parameter conditions of Examples 1-14

[0056]

[0057]

[0058] Comparative Example 1 refers to the preparation method and application parameter conditions in Example 1, except that only waste porcelain powder is used as raw material.

[0059] Comparative Example 2 refers to the preparation method and application parameter conditions in Example 1, except that the time for the first wet ball milling is 0.5 h, and the time for the second wet ball milling is 2 h.

[0060] Comparative Example 3 refers to the preparation method and application parameter conditions in Example 1, except that the time for the first wet ball milling is 8 hours, and the time for the second wet ball milling is 12 hours.

[0061] Example 15 Color Difference Test

[0062] The color difference of Examples 1-14 and Comparative Examples 1-3 was tested using an American X-Rite Ci60 colorimeter to detect the color difference before and after the ceramic repair. When measuring, the standard to be used was selected, the measurement port of the colorimeter was aimed at the ceramic, and the instrument was pressed to start the test. The value displayed on the screen after the measurement was completed was the color difference test result. When ΔE < 1, and ΔL, Δa and Δb are within ± 0.8, the color difference is qualified, and the results are shown in Table 2.

[0063] Table 2 Color difference test of Examples 1-14 and Comparative Examples 1-3

[0064]

[0065]

[0066] It can be seen from Table 1 that in Comparative Example 1, only waste porcelain powder is used as raw material, and the color difference before and after repair is large, so other components need to be introduced to reduce the color difference of the ceramic after repair; in Comparative Examples 2-3, the ball milling time determines the fineness of the composite porcelain powder. If the fineness is too coarse, the dry patching mud and the green body will not be tightly bonded, resulting in a large color difference after calcination. If the fineness is too fine, it is easy to cause secondary cracking after calcination. In Examples 1-14, when the weight ratio of waste porcelain powder, embryo powder and glaze powder is changed, and the amount of composite porcelain powder and the time of wet ball milling remain unchanged, the color difference first decreases and then increases. When the weight ratio of waste porcelain powder, embryo powder and glaze powder is 7:1:0.5, the color difference of Example 3 is the smallest; when the weight ratio of waste porcelain powder, embryo powder and glaze powder is 7:1:0.5, the amount of composite porcelain powder is changed, and the ball milling time remains unchanged, the color difference is the smallest when the amount of composite porcelain powder is 64 parts, among which the color difference of Example 6 is the smallest; when the weight ratio of waste porcelain powder, embryo powder and glaze powder is 7:1:0.5, the amount of composite porcelain powder is 64 parts, the time of the first wet ball milling is changed, and the time of the second wet ball milling remains unchanged, the color difference of Example 9 is the smallest, and the time of the first wet ball milling is 3h; when the weight ratio of waste porcelain powder, embryo powder and glaze powder is 7:1:0.5, the amount of composite porcelain powder is 64 parts, the time of the first wet ball milling is changed, and the time of the second wet ball milling remains unchanged, the color difference of Example 9 is the smallest, and the time of the first wet ball milling is 3h; The weight ratio of the material and the glaze powder is 7:1:0.5, the amount of composite porcelain powder is 64 parts, the time of the first wet ball milling is 3h, and when the time of the second wet ball milling is changed, the color difference is the smallest when the time of the second wet ball milling is 6h, among which the color difference of Example 12 is the smallest, and there is almost no color difference. This is because the waste porcelain powder is mixed with the body powder and the glaze powder, and the chemical composition thereof is highly similar to the chemical composition of the body, which can effectively fill the cracks of the body and maintain a highly similar color, so that the color difference of the repaired ceramic is small; controlling the time of wet ball milling is equivalent to controlling the fineness of the raw material. Maintaining the appropriate fineness can make the dry patch mud more closely combined with the body, and the color difference after calcination is small; and the use of waste porcelain powder is a secondary utilization of discarded porcelain pieces, which reduces environmental pollution, saves resources, and effectively improves production efficiency.

[0067] Examples 16-33

[0068] Referring to the preparation method and application parameter conditions in Example 12, the difference lies in that the preparation parameters of the improved reinforcing agent and the moisture content of the dry sludge are changed, as shown in Table 3.

[0069] Table 3 Parameter conditions of Example 12 and Examples 16-33

[0070]

[0071]

[0072] Comparative Example 4 refers to the preparation method and application parameter conditions in Example 12, except that only mullite is used as a reinforcing agent.

[0073] Comparative Example 5 refers to the preparation method and application parameter conditions in Example 12, except that the moisture content of the dry sludge is 50%.

[0074] Comparative Example 6 refers to the preparation method and application parameter conditions in Example 12, except that the moisture content of the dry sludge is 5%.

[0075] Example 34 High temperature resistance test

[0076] Example 12, Examples 16-33 and Comparative Examples 4-6 were observed to see whether cracking occurred after calcination. The results are shown in Table 4.

[0077] Table 4 High temperature resistance test of Example 12, Examples 16-33 and Comparative Examples 4-6

[0078]

[0079]

[0080] It can be seen from Table 4 that in Comparative Example 4, only mullite is added, and the repaired ceramic still has fine cracks, indicating that the single mullite is not effective enough to improve the high temperature resistance and needs to be modified; in Comparative Examples 5-6, the ceramics cracked significantly after repair, because the moisture content of the dry patching mud is too high, which increases the difficulty of repairing, and it is easy to collapse after calcination, and the repair effect is poor; the moisture content of the dry patching mud is too low, the green body and the dry patching mud are not easy to bond, and it is easy to cause cracking after calcination, and the high temperature resistance is poor. In Example 12 and Examples 16-33, when the amount of mullite was changed, the amount of acrylate copolymer and improved reinforcing agent, the stirring time and the moisture content of dry filler remained unchanged, the repaired ceramics all cracked, and when the amount of mullite was 16 parts, the cracks in Example 17 were smaller; when the amount of mullite was 16 parts, the amount of acrylate copolymer was changed, the stirring time, the amount of improved reinforcing agent and the moisture content of dry filler remained unchanged, the repaired ceramics all had cracks, and when the amount of acrylate copolymer was 3 parts, the cracks in Example 21 were smaller; when the amount of mullite was 16 parts, the amount of acrylate copolymer was 3 parts, the stirring time was changed, the amount of improved reinforcing agent and the moisture content of dry filler remained unchanged, the cracks in Example 24 were the smallest, and the stirring time was 5 hours; when the amount of mullite was 16 parts, the amount of acrylate copolymer was 3 parts, and the stirring time was 5 hours , when the dosage of the improving and reinforcing agent is changed and the moisture content of the dry filler remains unchanged, the crack of Example 27 is the smallest, and the dosage of the improving and reinforcing agent is 13 parts at this time; when the dosage of mullite is 16 parts, the dosage of the acrylate copolymer is 3 parts, the stirring time is 5h, the dosage of the improving and reinforcing agent is 13 parts, and the moisture content of the dry filler is changed, Example 31 does not crack when the moisture content of the dry filler is 15%. This is because the mullite in the improving and reinforcing agent has the advantages of low shrinkage and low expansion, and the repaired ceramic is not easy to crack, which effectively improves the high temperature resistance of the repaired ceramic; adding acrylate copolymer to modify mullite and potassium feldspar effectively improves the adhesion of the dry filler, so that the green body and the dry filler are more closely combined, it is not easy to crack after calcination, and the service life is increased; the appropriate moisture content of the dry filler can enable the dry filler to maintain good adhesion, so that the green body and the dry filler are closely combined, and ultimately extend the life of the ceramic.

[0081] Examples 35-49

[0082] Referring to the preparation method and application parameter conditions in Example 31, the difference is that the amount of the composite fiber and dispersant mixture and the proportion of each component therein are changed, as shown in Table 5.

[0083] Table 5 Parameters and conditions of Example 31 and Examples 35-49

[0084]

[0085] Comparative Example 7 refers to the preparation method and application parameter conditions in Example 31, except that no composite fiber is added.

[0086] Comparative Example 8 refers to the preparation method and application parameter conditions in Example 31, except that no dispersant mixture is added.

[0087] Example 50 Wear Test

[0088] Example 31, Examples 35-49 and Comparative Examples 7-8 were polished for 24 hours and the wear amount was tested. The results are shown in Table 6.

[0089] Table 6 Wear test of Example 31, Examples 35-49 and Comparative Examples 7-8

[0090] Example <![CDATA[Wear volume in 24 hours / cm 3 > Embodiment 31 3.2 Embodiment 35 3.0 Embodiment 36 2.9 Embodiment 37 3.1 Embodiment 38 3.2 Embodiment 39 2.8 Embodiment 40 2.7 Embodiment 41 2.9 Embodiment 42 3.0 Embodiment 43 2.5 Embodiment 44 2.4 Embodiment 45 2.6 Embodiment 46 2.3 Embodiment 47 2.0 Embodiment 48 2.2 Embodiment 49 2.4 Comparative Example 7 3.5 Comparative Example 8 3.3

[0091] As can be seen from Table 6, in Comparative Example 7, no composite fiber is added, and the ceramic wear after repair is large, and the life of the ceramic is short at this time; in Comparative Example 8, no dispersant mixture is added, and the components in the dry patching mud are easy to agglomerate, resulting in lumps, and the ceramic wear after repair is large. In Example 31 and Examples 35-49, when the weight ratio of polypropylene fiber, polyester fiber and carbon fiber is changed, the amount of composite fiber, the weight ratio of polyvinyl alcohol and polycarboxylic acid, and the amount of dispersant mixture remain unchanged, the wear first decreases and then increases. When the weight ratio of polypropylene fiber, polyester fiber and carbon fiber is 5:2:1, the wear is the smallest. At this time, the wear of Example 36 is 2.9 cm 3 When the weight ratio of polypropylene fiber, polyester fiber and carbon fiber is 5:2:1, the amount of composite fiber is changed, the weight ratio of polyvinyl alcohol and polycarboxylic acid and the amount of dispersant mixture remain unchanged, the wear amount of Example 40 is the smallest, which is 2.7 cm 3 , at this time, the amount of composite fiber is 5 parts; when the weight ratio of polypropylene fiber, polyester fiber and carbon fiber is 5:2:1, the amount of composite fiber is 5 parts, the weight ratio of polyvinyl alcohol and polycarboxylic acid is changed, and the amount of dispersant mixture remains unchanged, the wear amount is the smallest when the weight ratio of polyvinyl alcohol and polycarboxylic acid is 8:2, and the wear amount of Example 44 is 2.4 cm 3 When the weight ratio of polypropylene fiber, polyester fiber and carbon fiber is 5:2:1, the amount of composite fiber is 5 parts, the weight ratio of polyvinyl alcohol and polycarboxylic acid is 8:2, and the amount of dispersant mixture is changed, the wear amount of Example 47 is the smallest when the amount of dispersant mixture is 0.8 parts, which is 2.0 cm 3Because the composite fiber can increase the bonding force between the dry filler and the ceramic body, the network structure inside the fiber helps to enhance the adhesion of the dry filler, thereby enhancing the wear resistance of the repaired ceramic and extending the life of the ceramic; the dispersant mixture allows the components to be evenly dispersed, preventing the occurrence of agglomeration, and there will be no uneven drying during the ceramic body repair process, thereby enhancing the wear resistance of the repaired ceramic and increasing the life of the repaired ceramic.

[0092] Examples 51-63

[0093] Referring to the preparation method and application parameter conditions in Example 47, the difference is that the preparation parameters of the modified thickener and the amount of the modified thickener are changed, as shown in Table 7.

[0094] Comparative Example 9 refers to the preparation method and application parameter conditions in Example 47, except that no modified thickener is added.

[0095] Example 64 Water absorption test

[0096] Example 47, Examples 51-63 and Comparative Example 9 were dried at 105°C to constant weight; the dried samples were immersed in water for 24 hours; the samples were taken out and the surface moisture was gently wiped off; the weight after immersion was measured. The calculation was specifically based on the following formula: water absorption rate (%) = (weight after immersion - weight after drying) / weight after drying × 100%. The results are shown in Table 7.

[0097] Table 7 Water absorption test of Example 47, Examples 51-63 and Comparative Example 9

[0098]

[0099]

[0100] It can be found from Table 7 that no modified thickener was added in Comparative Example 9, and the water absorption rate was 0.51%, which exceeded the industry standard, and the repaired ceramic did not meet the standard. In Examples 47 and 51-63, when the amount of methyl cellulose was changed, the amount of diisocyanate, the temperature of the cross-linking reaction and the amount of the modified thickener remained unchanged, the water absorption first decreased and then increased. When the amount of methyl cellulose was 5 parts, the water absorption of Example 53 was the smallest, which was 0.29%; when the amount of methyl cellulose was 5 parts, the amount of diisocyanate was changed, the temperature of the cross-linking reaction and the amount of the modified thickener remained unchanged, the water absorption was the smallest when the amount of diisocyanate was 1.5 parts, and the water absorption of Example 56 was 0.23%; when the amount of methyl cellulose was 5 parts, the amount of diisocyanate was 1.5 parts, the temperature of the cross-linking reaction was changed, and the amount of the modified thickener remained unchanged, the water absorption of Example 59 was the smallest. This is because the temperature of the cross-linking reaction will affect the performance of the final modified thickener, thereby affecting the water absorption of the repaired ceramic. rate; when the amount of methyl cellulose is 5 parts, the amount of diisocyanate is 1.5 parts, the temperature of the cross-linking reaction is 125°C, when the amount of modified thickener is changed, the water absorption rate is the smallest when the amount of modified thickener is 0.2 parts, and the water absorption rate of Example 61 is 0.13%. This is because the cross-linking reaction of the mixture of methyl cellulose and hydroxypropyl methyl cellulose can improve the performance of the thickener, and by changing the parameters in the preparation process, the viscosity and adhesion of the dry filler can be improved, and the repaired ceramics can be made denser and the surface smoother, thereby reducing the water absorption rate of the repaired ceramics, reducing the erosion of the ceramics by water, and extending the life of the ceramics; controlling the amount of modified thickener can make the dry filler have the strongest adhesion, make the dry filler more tightly bonded at the cracks of the green body, reduce the water absorption rate of the repaired ceramics, and enhance the durability of the repaired ceramics.

[0101] Examples 65-76

[0102] Referring to the preparation method and application parameter conditions in Example 61, the difference is that the amount of calcium silicate used and the parameters in the ceramic body repair process are changed, as shown in Table 8.

[0103] Table 8 Parameters and conditions of Example 61 and Examples 65-76

[0104]

[0105]

[0106] Comparative Example 10 refers to the preparation method and application parameter conditions in Example 61, except that no calcium silicate is added.

[0107] Comparative Example 11 refers to the preparation method and application parameter conditions in Example 61, except that the treatment depth is 0 mm.

[0108] Comparative Example 12 refers to the preparation method and application parameter conditions in Example 61, except that the processing depth is 6 mm.

[0109] Comparative Example 13 refers to the preparation method and application parameter conditions in Example 61, except that the firing temperature is 1500°C and the firing time is 30 hours.

[0110] Comparative Example 14 refers to the preparation method and application parameter conditions in Example 61, except that the firing temperature is 800°C and the firing time is 10 hours.

[0111] Example 77 Compressive Strength and Flexural Strength Test

[0112] The compressive strength is tested using a compression tester, which gradually applies pressure until the repaired ceramic is damaged; the following formula is used to calculate: σ = P / A. In the formula, σ is the compressive strength (MPa); P is the maximum load applied (N); A is the force-bearing area of ​​the sample (mm 2 ).

[0113] The flexural strength was tested using a three-point bending test device, with uniform force applied in the middle of the sample until the repaired ceramic was damaged or deformed significantly; the following formula was used to calculate: Flexural strength (MPa) = 3PL / 2bd 2 Where P is the maximum applied load (N); L is the support distance (mm); b is the specimen width (mm); and d is the specimen thickness (mm).

[0114] The results are shown in Table 9 and Figure 1 shown.

[0115] Table 9 Compressive strength and flexural strength tests of Example 61, Examples 65-76 and Comparative Examples 10-14

[0116]

[0117]

[0118] From Table 9 and Figure 1It can be found that when calcium silicate is not added in comparative example 10, the compressive strength and flexural strength of the repaired ceramic are significantly reduced. This is because it can form a more stable phase during the firing process, thereby improving the overall structural strength of the repaired ceramic. It itself also has a certain corrosion resistance, which effectively extends the life of the repaired ceramic; in comparative examples 11-12, the compressive strength and flexural strength are weak. This is because too shallow a treatment depth may cause the dry filler mud to be unable to provide sufficient support, resulting in a loose direct bond with the ceramic body. Too deep a treatment depth may cause local material instability, thereby affecting the strength of the repaired ceramic; the compressive strength and flexural strength of comparative examples 13-14 are very low. This is because too high a firing temperature will affect the internal structure of the ceramic, reducing the compressive strength and flexural strength, and will also cause excessive shrinkage of the ceramic, resulting in secondary cracking. Too low a firing temperature will cause the dry filler mud to be loosely bonded to the ceramic body, resulting in low compressive strength and flexural resistance at the cracks, and a short service life. In Example 61 and Examples 65-76, when the amount of calcium silicate is changed, the treatment depth, firing temperature and time remain unchanged, the compressive strength and flexural strength first increase and then decrease. When the amount of calcium silicate is 0.08 parts, the strength of Example 65 is the largest, the compressive strength is 115.2MPa, and the flexural strength is 26.0MPa; when the amount of calcium silicate is 0.08 parts, the treatment depth is changed, the firing temperature and time are unchanged, the compressive strength and flexural strength first increase and then decrease. When the treatment depth is 2.0mm, the strength of Example 68 is the largest, the compressive strength is 115.9MPa, and the flexural strength is 26.4MPa; when the amount of calcium silicate is 0.08 parts, the treatment depth is 2.0mm, the firing temperature is changed, and the firing time is unchanged, the compressive strength and flexural resistance are the largest at a firing temperature of 1120°C. , the compressive strength of Example 71 is 117.1MPa, and the flexural strength is 27.5MPa; when the amount of calcium silicate is 0.08 parts, the treatment depth is 2.0mm, and the firing temperature is 1120℃, when the firing time is changed, Example 75 reaches the maximum compressive strength and flexural strength when the firing time is 22h. At this time, the compressive strength is 118.2MPa and the flexural strength is 28.4MPa. This is because the appropriate amount of calcium silicate can improve the overall strength of the repaired ceramic; the appropriate treatment depth can ensure that the dry fill mud is fully penetrated and firmly bonded to the cracks, thereby enhancing the overall strength of the repaired ceramic; the appropriate firing temperature and time ensure that the dry fill mud is completely combined with the internal structure of the ceramic body, the ceramic will not undergo secondary cracking, the compressive strength and flexural strength are improved, and the life of the repaired ceramic is extended.

[0119] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing dry patching mud for ceramic repair, characterized in that: The preparation method of the dry patching mud for ceramic repair is as follows: Putting the discarded porcelain pieces into a pulverizer for pulverization to obtain waste porcelain powder; mixing the waste porcelain powder, green body powder and glaze powder to obtain composite porcelain powder; An improved reinforcing agent is obtained by adding an acrylic acid ester copolymer to a mixture of mullite and potassium feldspar for modification; Adding diisocyanate to a mixture of methylcellulose and hydroxypropylmethylcellulose for cross-linking reaction to obtain a modified thickener; 62-66 parts of the composite ceramic powder, 11-15 parts of the improved reinforcing agent and 3-7 parts of the composite fiber are weighed by weight, and wet-milled for 2h-5h using 30 parts of deionized water as a medium, so that the number of particles with a particle size of 15 μm reaches more than 65%, to obtain slurry A; Add 0.6-1 parts of the dispersant mixture, 0.1-0.4 parts of the modified thickener and 0.07-0.1 parts of calcium silicate to the slurry A, and perform secondary wet ball milling for 5h-8h to obtain slurry B; The mud B is naturally dried until the moisture content is 13%-17% to obtain the dry mud for ceramic repair.

2. The method for preparing dry patching mud for ceramic repair according to claim 1, characterized in that: The weight ratio of the waste porcelain powder, the green body powder and the glaze powder is 5-8:1:0.

5.

3. The method for preparing dry patching mud for ceramic repair according to claim 2, characterized in that: The chemical composition of the waste porcelain powder is 63.2% SiO2, 18.8% Al2O3, 8.1% CaO, 4.5% MgO, 1.3% Fe2O3, 2.1% K2O, 0.9% Na2O and 1.1% TiO2; the chemical composition of the green body powder is 62.7% SiO2, 27.4% Al2O3, 5.3% CaO, 2.0% MgO, 0.7% Fe2O3, 0.7% K2O, 0.8% Na2O and 0.4% TiO2; the chemical composition of the glaze powder is 61.3% SiO2, 14.5% Al2O3, 13.1% CaO, 2.6% MgO, 1.9% Fe2O3, 3.7% K2O, 2.5% Na2O and 0.4% TiO2.

4. The method for preparing dry patching mud for ceramic repair according to claim 1, characterized in that: The preparation method of the improved reinforcing agent is specifically as follows: 14-18 parts of the mullite and 4 parts of the potassium feldspar are ground until the particle size reaches 10 μm to obtain a mixed powder; 1-4 parts of the acrylic ester copolymer and 8 parts of deionized water are added to the mixed powder, followed by stirring for 3-6 hours until the mixture is uniformly mixed to obtain the improved reinforcing agent.

5. The method for preparing dry patching mud for ceramic repair according to claim 1, characterized in that: The preparation method of the modified thickener is specifically as follows: adding 2-6 parts of the methyl cellulose and 3 parts of the hydroxypropyl methyl cellulose to 6 parts of deionized water, stirring until uniform dispersion, and obtaining a cellulose mixture; adding 0.5-2 parts of the diisocyanate to the cellulose mixture, stirring for 1 hour, and obtaining a thickener precursor; transferring the thickener precursor to a reaction kettle, performing a cross-linking reaction at 115° C.-130° C. for 3 hours, and cooling and centrifugal drying to obtain the modified thickener.

6. The method for preparing dry patching mud for ceramic repair according to claim 1, characterized in that: The composite fiber is a mixture of polypropylene fiber, polyester fiber and carbon fiber; the weight ratio of the polypropylene fiber, the polyester fiber and the carbon fiber is 3-7:2:

1.

7. The method for preparing dry mortar for ceramic repair according to claim 1, characterized in that: The dispersant mixture is a mixture of polyvinyl alcohol and polycarboxylic acid; the weight ratio of the polyvinyl alcohol to the polycarboxylic acid is 6-9:

2.

8. An application of dry patching mud for ceramic repair, characterized in that: The dry patching mud prepared by the preparation method according to any one of claims 1 to 7 is applied to the ceramic body for repairing in the following steps: S1: cleaning the cracks of the green body to remove ash and impurities present in the cracks of the green body, wherein the cleaning depth is 1.5-2.5 mm; S2: wetting the cracks of the green body with deionized water, and naturally drying the cracks of the green body; S3: Fill part of the dry patching mud into the crack of the green body and compact it, then continue to fill the dry patching mud until the compacted part is higher than the green body surface around the patching part, and wet the patching part and the surrounding part with deionized water; After S4 is naturally dried, the raised part of the surface of the blank is scraped off and the repaired part is polished. Then it is glazed and put into the kiln. It is fired at temperature TE1 for TI1 time to finally complete the ceramic repair.

9. The use of dry filler mud for ceramic repair according to claim 8, characterized in that: The height above the surface of the blank around the repaired part in S3 is 1 mm.

10. The use of dry mortar for ceramic repair according to claim 8, characterized in that: The temperature TE1 in S4 is 1100° C.-1140° C.; the TI1 time is 20-23 h.

Citation Information

Patent Citations

  • Blank for mending ceramic paste preforms and preparation method and mending process thereof

    CN101717268B

  • Blank Repair Mud for Ceramic Green Bodies, Its Preparation Method and Application

    CN106083018B

  • Blank for mending ceramic paste preforms and preparation method and mending process thereof

    CN101717268A

  • Reproducible repair method for micro cracks of Nixing pottery

    CN108456006A

  • Repair method of continuous oxide fiber reinforced oxide ceramic matrix composite material

    CN113999056A

Cited By

  • Dry repairing mud for repairing ceramic disc forming mold as well as preparation method and application of dry repairing mud

    CN121248307A